Genre - Based Approach for Writing Recount Text at MTs "Darul Ulum" Karang Pandan, Pasuruan - Hidayat, Ratih Wulandari; Setyowati, Lestari; Mabaroh, Barotun (Jurnal Bahasa Lingua Scientia, 2018)
Among other skills, writing is often seen as a difficult skill for English as a Foreign Language (EFL) learners.Â  In particular, writing seems to be a difficult subject for the students of MTs. Darul Karangpandan Pasuruan. It could be seen from the result of the preliminary study, which showed that the ability of the eight grade students of MTs. DarulUlumKarangpandan in writing paragraphs was still poor. This research was aimed at improving the studentsâ ability in writing recount text through Genre-Based Approach (GBA) at eight grade of MTs. Darul Ulum Karangpandan. The research design of this study was action research.Â  The instruments used in this study were interview, observation checklist, and test.Â  The results of the research demonstrate that the studentsâ mean scores gradually improved from 56.51 in the pre-test to 71.31 in Cycle I and to 77.82 in Cycle II. These achievements prove that the implementation of genre-based approach was successful in improving the studentsâ ability in writing recount text.Â